A LEGAL PROTECTION OF INDONESIAN NON-PROCEDURAL MIGRANT WORKERS INVOLVED IN ILLEGAL ACTIVITIES OF THE ONLINE SCAMMER IN CAMBODIA - Earlyana, Nabila; Aung, Kyi Lei Lei (Indonesian Journal of Labour Law and Industrial Relations, 2025)
The increasing phenomenon of non-procedural Indonesian Migrant Workers (PMI) involved in Illegal activities such as online scamming is an increasingly worrying issue that requires serious attention. Because their departure is unofficial, the legal protection they receive is very limited. However, this does not necessarily eliminate their right to protection. Several international legal bases still provide room for protection, including the active and passive national principle, the principle of good faith of the state towards its citizens, the Articles on State Responsibility issued by the International Law Commission (ILC) in 2001, and the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families in 1990. In addition to legal instruments, bilateral settlements between countries are also an important aspect in handling this phenomenon. Without good cooperation and coordination between sending and receiving countries, efforts to eradicate this practice will be difficult to achieve optimally.